Lean and agile project management : how to make any project better, faster, and more cost effective, second edition - Vanzant Stern, Terra (New York : Routledge, 2020)
"When project managers are faced with budget cuts and fewer resources, waste elimination becomes a priority in maintaining effectiveness. This does not mean shortening or abandoning traditional project cycles. In fact, fast results on critical assignments can only be completed with strong plans and a detailed work-breakdown structure. The connections, or lack thereof, are what strongly impact performance and quality. Lean and Agile, as covered in this book, is meant to enhance traditional project management not replace the science. A strong foundation in traditional project management is necessary to appreciate the benefits of adopting Lean and Agile. Lean and Agile Project Management: How to Make Any Project Better, Faster, and More Cost Effective defines the wastes and issues found in project management and demonstrates how they can be addressed by engaging Lean Thinking and Agile Techniques. This book also: Shows how to apply Lean principals to project management (PM) Teaches the application of simple Six Sigma metrics in PM Discusses the adoption of Agile techniques in PM in order to stay on task and remain flexible Helps readers discover the theoretical synergies between popular PM programs Promotes an understanding of how Lean people skills can help a person become a better leader and manager Since the publication of the first edition of this book, the bodies of knowledge have all been systematically updated. In addition, through conducting peer groups and detailed workshops, the author has simplified many of the basics and they are now much easier to understand. Essentially, the author believes traditional project management can benefit from adding Lean and Agile, but she has simplified the model for greater efficiency"--
"A Productivity Press Book"--Title page.
Revised edition of the author's Lean and agile project management, [2017].
OCLC-licensed vendor bibliographic record.
Keywords: Agile project management; Project management; Lean manufacturing; Cost effectiveness; Six sigma (Quality control standard)